Asuhan keperawatan pada ibu hamil yang mengalami anemia dengan intervensi jus bayam dan tomat - Muhammad Irgi; Aryanti Wardiyah; Rilyani Rilyani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Anemia in pregnant women carries the risk of giving birth to a baby that is not yet full term (premature), miscarriage, bleeding both before and after delivery, uneventful delivery, fetal death in the womb, death of the pregnant woman, and convulsions during pregnancy. In October 2023-January 2024 the Kedaton Community Health Center had a total of 733 pregnant women and it was found that 76 pregnant women were anemic. Purpose : to make a report on maternity nursing care by giving spinach and tomato juice to increase hemoglobin levels in pregnant women who experience anemia in Kedaton District, Bandar Lampung City in 2025 Method: This type of research uses qualitative descriptive research. The research design uses a descriptive research approach and a nursing care case study approach, which includes assessment, nursing diagnosis, planning, implementation, and evaluation. This case study is the application of spinach and tomato juice therapy by Maternity Nursing Care to increase hemoglobin levels Results: Both respondents experienced significant changes, namely in Mrs. P with a difference of 1.5 g/dL, while Mrs. A with a difference of 1.8 g/dL. From the results of the analysis of hemoglobin levels, the author concluded that there was a significant increase in hemoglobin levels in pregnant women. Conclusion: Giving spinach and tomato juice can increase hemoglobin levels in pregnant women